2020
DOI: 10.1128/jvi.00924-20
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 and Methamphetamine-Mediated Mitochondrial Damage and Neuronal Degeneration in Human Neurons

Abstract: Methamphetamine, a potent psychostimulant, is a highly addictive drug commonly used by persons living with HIV (PLWH), and its use can result in cognitive impairment and memory deficits long after its use is discontinued. Although the mechanism(s) involved with persistent neurological deficits are not fully known, mitochondrial dysfunction is a key component in methamphetamine neuropathology. Specific mitochondrial autophagy (mitophagy), and mitochondrial fusion and fission are protective quality control mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Furthermore, a cross-species study demonstrated that HIV in humans and gp120 in mice impaired learning and executive functions which were worsened by Meth abuse in both species [6]. Although exact mechanisms for Meth exacerbation of HIV/gp120-associated neurocognitive impairment remain ambiguous, various possibilities have been proposed including, but are not limited to, oxidative stress [78,79], microglia activation and resultant neural injury [19,38,39], disruption of the blood-brain barrier [80, 81] and synaptodendritic dysfunction and damage in the adult cortex and hippocampus [24,26]. Our results showed the synergic effect of Meth and gp120 on LTP was signi cantly attenuated by Ac-YVAD-CMK, a potent and irreversible inhibitor of the in ammatory enzyme caspase-1 [41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a cross-species study demonstrated that HIV in humans and gp120 in mice impaired learning and executive functions which were worsened by Meth abuse in both species [6]. Although exact mechanisms for Meth exacerbation of HIV/gp120-associated neurocognitive impairment remain ambiguous, various possibilities have been proposed including, but are not limited to, oxidative stress [78,79], microglia activation and resultant neural injury [19,38,39], disruption of the blood-brain barrier [80, 81] and synaptodendritic dysfunction and damage in the adult cortex and hippocampus [24,26]. Our results showed the synergic effect of Meth and gp120 on LTP was signi cantly attenuated by Ac-YVAD-CMK, a potent and irreversible inhibitor of the in ammatory enzyme caspase-1 [41].…”
Section: Discussionmentioning
confidence: 99%
“…This axon injury, in turn, could affect action potential signal transmission [ 112 ] or lead to a reduction in nerve conduction velocity [ 113 ]. Besides, gp120 and Tat in combination with METH induced focal swellings of dendrites and reduced the total length of the neuritic network in human primary neurons [ 50 ]. Data from animal studies suggested that loss or alteration of dendritic spines resulting from METH treatment of HIV-1 gp120 tg mice led to impaired learning and memory [ 40 ].…”
Section: Potentiation Of Neuroinflammation By the Combination Of Hiv-1 Infection And Methamphetamine Usementioning
confidence: 99%
“…Dynamin-related protein 1 (DRP1) is the central molecular player that mediates mitochondrial fission. METH has been found to increase mitochondrial fragmentation through translocation of DRP1 in HIV-1-treated human primary neurons [ 50 ]. The impaired mitophagy detected in the presence of METH in combination with HIV-1 gp120 or Tat proteins in this study suggests its possible association with the accelerated aging observed in HIV-1-infected individuals.…”
Section: Potentiation Of Neuroinflammation By the Combination Of Hiv-1 Infection And Methamphetamine Usementioning
confidence: 99%
“…36,37 METH has been reported to cause mitochondrial dynamics disorder and degeneration in neural cells. [38][39][40] However, it remains unknown whether RIP3 can cause METH-induced programmed necrosis by activating Drp1 to cause increased mitochondrial division.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial fission dysregulation can produce spherical mitochondria or fragmented mitochondria and induce cristae remodelling, which is characterized by the breakage and disappearance of cristae 36,37 . METH has been reported to cause mitochondrial dynamics disorder and degeneration in neural cells 38‐40 . However, it remains unknown whether RIP3 can cause METH‐induced programmed necrosis by activating Drp1 to cause increased mitochondrial division.…”
Section: Introductionmentioning
confidence: 99%